2001
DOI: 10.1046/j.1439-0523.2001.00609.x
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism and inheritance of intraflower self‐pollination in self‐pollinating variant strains of periwinkle

Abstract: The mechanism and inheritance of intraflower self‐pollination in self‐pollinating variant strains of periwinkle was studied using three self‐pollinating and two non‐self‐pollinating but fully self‐fertile strains. Intraflower self‐pollination in self‐pollinating strains occurred due to the continued growth of the gynoecium beyond the base of the anthers, even after anthesis, resulting in intraflower self‐pollination. In non‐self‐pollinating strains, the stigma remained below the base of the anthers and did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Parental plants were raised in a glass house from seeds produced by artificial self-pollination. Reciprocal crosses were also made as described earlier (Kulkarni et al, 2001). The F 1 plants were selfed and also backcrossed to both the parents.…”
Section: Methodsmentioning
confidence: 99%
“…Parental plants were raised in a glass house from seeds produced by artificial self-pollination. Reciprocal crosses were also made as described earlier (Kulkarni et al, 2001). The F 1 plants were selfed and also backcrossed to both the parents.…”
Section: Methodsmentioning
confidence: 99%
“…It was crossed with a white flowered variety, Nirmal. In an earlier study the flower colour genotype of Nirmal (W) was found to be rrWW [11]. Parent plants were raised in a glasshouse from seeds obtained by artificial self-pollination pollen is powdery and the flowers are easily selfed by a means of a blunt needle inserted into the top of the tube [9].…”
Section: Methodsmentioning
confidence: 99%
“…Altogether 195,103 and 93 plants of F2, and two backcrosses, F1xV and F1x W respectively, were scored for corolla color, along with 10 plants each of the parental and F1 generations. Chi-square were used for testing the goodness-of-fit of observed and expected frequencies of different phenotypic classes in the F2 and backcross generations by Kulkarni, Sreevalli et al (2001) [11].…”
Section: Methodsmentioning
confidence: 99%
“…A mutagenized population was produced that is suitable for screening by genetic techniques such as TILLING [19][20][21].…”
Section: Overall Characteristics Of P Hybrida Mutagenized Populationsmentioning
confidence: 99%